Association between lifestyle, dietary, reproductive, and anthropometric factors and circulating 27-hydroxycholesterol in EPIC-Heidelberg - Le Cornet, Charlotte; Johnson, Theron S.; Lu, Dalin; Kaaks, Rudolf; Turzanski Fortner, Renée (Cancer causes & control, 2020)
Given that 27-hydroxycholesterol (27HC) is the first identified endogenous selective estrogen receptor modulator, the aim of this study was to investigate the extent to which dietary or lifestyle factors impact circulating 27HC concentrations in a large-scale setting.
Gesehen am 31.03.2020